Effect of the planar center moiety for a donor-acceptor polymeric electrochrome. (13th January 2017) - Doyranlı, Ceylan; Çolak, Betül; Lacinel, Gözde; Can, Mustafa; Koyuncu, Fatma Baycan; Koyuncu, Sermet
Abstract: In this work, phenanthrene centered donor-acceptor monomer; 5, 10-bis(4-hexyl-2-thienyl)phenantro[9, 10-c][1, 2, 5]thiodiazole; MES16 was synthesized and then its electrochromic application of corresponding polymer was carried out. 4, 7-di(thiophen-2-yl)-2, 1, 3-benzothiadiazole (TST) was also synthesized as a standard molecule to determine the effect of the planar phenanthrene center on electrochromic performance. Electrochemical properties were elucidated by cyclic voltammetry and then HOMO-LUMO band gaps were calculated by using their oxidation and reduction onset potentials. Finally, electrochromic properties of poly-(MES16) and poly-(TST) were investigated via spectro-electrochemical measurements. DFT calculations exhibit that poly-(MES16) has a high planarity and an intramolecular charge transfer from the polymer backbone-donor to thiadiazole-acceptor subunit. Because of high solid state π−π interactions of the poly-(MES16), a good quality film was obtained corresponding to self-assembly property planar phenantrene center. Owing to this property, electrochromic performance of poly-(MES16) such as response time, stability and ΔT% were better than the standard poly-(TST). Graphical abstract: Highlights: The planar phenantrene center effect on the electrochromic performance of a donor-acceptor polymer structure was investigated. The neutral state color converted the violet to yellow upon insertion of the phenantrene center instead of phenylene moiety. In comparison to TST standard polymer, poly-(MES16) has much better electrochromic performance especially high resistance to over oxidation.